Gerakan Perubahan (Renaissence) Oleh Dinasti Umayyah II (Islam di Andalusia) Terhadap Berkembangnya Intelektual dan Kebudayaan di Eropa - Mubadillah, Rosita (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The second period of the Umayyad dynasty, known as the Andalusian Umayyads, had a significant influence on the development of European civilization in the Middle Ages. After the fall of Damascus, this dynasty continued its rule in the Iberian Peninsula with its center in Cordoba. This article aims to analyze the influence of the Umayyad Dynasty II on Europe, especially in the fields of science, art, architecture and cross-cultural relations. The research method used in this article is a literature review, where literature study is a method that involves collecting, evaluating and synthesizing existing literature to answer research questions or understand a particular topic comprehensively. According to Danial and Warsiah, Literary Studies is research carried out by researchers by collecting a number of books and magazines related to research problems and objectives. The findings show that the Umayyad Dynasty in Andalusia not only contributed to the spread of Islamic knowledge, such as astronomy, medicine, and mathematics, but also became a catalyst for the development of science in Europe through intellectual transfer and translation of scientific texts. Apart from that, the architectural style promoted by the Umayyad II Dynasty played a role in the formation of European architectural styles, especially the Gothic and Romanesque styles. Through cultural interactions, the Umayyad II Dynasty introduced irrigation techniques, agriculture, and government systems that inspired European nations. The results of this study underline the importance of the influence of Islamic civilization in Andalusia in the development of European science and culture, which later became the foundation for the Renaissance.